Crossing the Mirror: an Approach to the Social Perception of the Prehistoric Past from a Gender Perspective - Mouriño, Andrea; Comendador, Beatriz (Filanderas, 2023)
The media is a system of immediate and effective communication, which forms a mass culture made up of symbols, myths and stereotypes of individuals as a form of «industrialised production of reality». Within the conceptual framework of Public Archaeology, from a critical and feminist perspective, an essay is presented to approach the social perception of the prehistoric past in contemporary Popular Culture. The purpose of this work is to analyse and conceptualise the messages and ideas generated by the mass culture around the representation of prehistoric humanity to understand how they are constructed and what kind of society they promote. To this end, the image of the cavewoman is approached from its configuration in the popular imaginary to analyse the stereotypes and sexisms installed, their origin, their repercussions on the social perception of prehistory and what role this idea plays in contemporary society, and more particularly, what implications they have for women. We must go through this distorted mirror and image of the past, created by the consumer society projecting its own, where the image of women is not only that of the past but also that of the future.